2011
DOI: 10.1007/s11240-011-0058-9
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolism in micropropagated Hypericum perforatum L. grown in non-aerated liquid medium

Abstract: Hypericum perforatum L. is a medicinal plant that has been extensively studied because of its bioactive properties. The objective of this study was to establish a system that could lower the cost of in vitro propagation by using liquid medium, as well as to evaluate the secondary metabolism in the systems tested. Nodal segments of H. perforatum were obtained from in vitro shoots and grown in three liquid culture systems: total immersion (TI), partial immersion (PI), and paper bridge support (PB). Semi-solid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 38 publications
4
29
0
Order By: Relevance
“…In our preliminary studies, agar cultures of the three cultivars of H. perforatum grown on MS medium variants accumulated several times lower amounts of free phenolic acids (unpublished). These results confirmed the observations of other research teams, which demonstrated that liquid media are better for the accumulation of phenolic compounds in H. perforatum in vitro systems (Savio et al 2012). Based on the results of the present study, agitated shoot cultures of the cultivar 'Helos' can be nominated as a rich, potential biotechnological source of the bioactive phenolic acids analyzed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our preliminary studies, agar cultures of the three cultivars of H. perforatum grown on MS medium variants accumulated several times lower amounts of free phenolic acids (unpublished). These results confirmed the observations of other research teams, which demonstrated that liquid media are better for the accumulation of phenolic compounds in H. perforatum in vitro systems (Savio et al 2012). Based on the results of the present study, agitated shoot cultures of the cultivar 'Helos' can be nominated as a rich, potential biotechnological source of the bioactive phenolic acids analyzed.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, numerous micropropagation protocols have been developed (Goel et al 2009;Savio et al 2012). Some of them can be useful in the production of elite varieties with predictable phytochemical profiles for pharmaceutical purposes (Murch and Saxena 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies with other medicinal plant species have also revealed that the liquid media increased production of metabolites such as lignans in shoot-differentiating callus cultures of Schisandra chinensis (Szopa et al 2016) and polyphenolic compounds in the Hypericum perforatum shoot liquid culture (Savio et al 2011). The elimination of agar from the culture medium also resulted in substantial savings in cost.…”
Section: Quantification Of Flavones and Verbascoside In Multiple Shootssupporting
confidence: 62%
“…However, S. alpina shoot tip explants placed in liquid culture, either agitated or stationary, did not derive shoots, and tissue necrosis was observed, probably caused by the continuous contact between the plant tissue and the liquid medium. In addition, Savio et al (2011) suggest that the limited gas exchange between tissue and environment may account for the low rate of multiplication observed for completely submerged Hypericum perforatum shoots in liquid culture. Also, Scutellaria latifolia and S. costaricana plantlets grown in an immersed liquid culture had a lower multiplication ratio than those on agar culture (Tascan et al 2010).…”
Section: Shoot Multiplicationmentioning
confidence: 99%
“…(Chan et al 2009); Hoslundia opposita Vahl. (Prakash and Van Staden 2007), Hypericum perforatum L. (Danova et al 2012;Savio et al 2012), Labisia pumila (Hartinie and Jualang 2007), Leptadenia reticulate (Kalidass et al 2008), Mollugo nudicaulis (Nagesh and Shanthamma 2011), Ornithogalum ulophyllum (Ozel et al 2008), Ocimum gratissimum L (Gopi et al 2006 A good example of such studies is on Rhodiola rosea that is an endangered medicinal species with a limited distribution. It has an outstanding importance for the pharmaceutical industry, in the prevention and cure of cancer, heart and nervous system diseases etc.…”
Section: Propagation By Shoot and Node Culturementioning
confidence: 99%